Experimental investigation on existing precast prc elements strengthened with cementitious composites - Pellegrino, Carlos; Giacomin, Giorgio; Perlo, Rafael Alberto (Alternativas, 2017)
A number of experimental investigations on fibre reinforced polymer (FRP), with the aim of understanding their behaviour when applied as strengthening of reinforced concrete elements, are available in the literature but very few information is available on strengthening real-scale elements with cementitious composites. In particular design code formulations are scanty or non-existent. In this study the behaviour of four precast pre-stressed TT beams taken from an existing industrial building was investigated. One of them was considered as control unstrengthened TT beam, whereas the others were strengthened with different techniques, namely with FRP laminates (glued with epoxy resin), carbon fibres with cementitious matrix and steel fibres with cementitious matrix. Each material involved in this study was also mechanically characterized to obtain the main physical properties. Adequate specimens were obtained from the existing TT beam to characterize the concrete and the reinforcing steel bars.